1998
DOI: 10.3141/1651-05
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fuzzy Logic to the Control of a Pedestrian Crossing Signal

Abstract: Fuzzy logic is known to be suited for dealing with a complex optimization problem with many objectives, many constraints, unclear input information, and vague decision criteria. Controlling the timing of a traffic signal falls in this category of problem. Fuzzy logic is introduced for controlling the timing of a pedestrian crossing signal. The controller is designed to emulate the decision process of an experienced crossing guard. The performance of this control is tested against two types of conventional dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…This leads to the learning-driven ITS. Some commonly used learning algorithms, including rough set theory [11], online learning [12], fuzzy logic [13], are used to extract intrinsic rules from historical and real-time traffic data. These kinds of work always run into challenges of computational efficiency when dealing with large data sets.…”
Section: Related Workmentioning
confidence: 99%
“…This leads to the learning-driven ITS. Some commonly used learning algorithms, including rough set theory [11], online learning [12], fuzzy logic [13], are used to extract intrinsic rules from historical and real-time traffic data. These kinds of work always run into challenges of computational efficiency when dealing with large data sets.…”
Section: Related Workmentioning
confidence: 99%
“…In recent decades, the applications of fuzzy logic in traffic signal control have been extensively investigated. After the first application of fuzzy logic in traffic signal control introduced by Pappis and Mamdani [22], many useful research findings about the fuzzy logic signal control have been reported [23,24]. Most of the cited studies are focusing on the application of fuzzy inference or fuzzy control in the real-time traffic signal settings.…”
Section: Introductionmentioning
confidence: 99%
“…So it may result in the waste of time and space resource of the traffic system. Then, actuated control was introduced to pedestrian crossing control (5,6). For the conventional demand-actuated control, the conventional method it that the green phase of vehicle is allowed to be extended as long as the headway of vehicle smaller than 4s, the green phase is terminated if the headway is larger than 4s.…”
Section: Introductionmentioning
confidence: 99%